Management of dystocia due to Schistosomus Reflexus - a case report - Rajoria, Jitendra Singh; Ningwal, Deepak; Singh, A P; Tomar, Priyanshu; Prashant; Tandia, Neelam (Animal Reproduction Update, 2023)
Schistosomare flexus are a major congenital anomaly which occurs during embryonic development. Schistosomare flexus are characterized by incomplete fusion of abdominal wall leading to exposed viscera and marked ventral curvature of spine. A genetic or chromosomal abnormality, mutation, chromosomal anomaly, infectious agent, or a combination of these factors may be the cause, although its etiology is unknown. A Holstein Friesian (HF) cross-bred cow of 4 years with straining and fetal intestine hanging through the vulva was presented to the veterinary clinical complex for parturition failure. Thus, it was diagnosed as a case of Schistosomare flexus. With per vaginal examination it was further confirmed that visceral organs were from the fetus. Therefore, it was decided to remove the fetus through caesarean section.